Pencegahan Stunting Berbasis Edukasi Ibu Balita, Pemberdayaan Kader Posyandu, dan Media Digital di Puskesmas Pauh Kota Padang: Stunting Prevention through Maternal Education, Empowerment of Posyandu Cadres, and Digital Media at Pauh Community Health Center, Padang City - Sri Siswati; Latifah Azzahra Nofrizal; Anggi Maisya Putri; Rahmi Putri Yulianti; Salwa Sayyidina Ningsih (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
Stunting remains a national public health priority in Indonesia, including in the working area of the Pauh Community Health Center, Padang City. Based on the 2024 report, 149 toddlers were identified as stunted, with the highest prevalence in Pisang Village (30 cases). Contributing factors include suboptimal parenting practices, limited maternal knowledge of child nutrition, and economic constraints. This community service aimed to improve mothers’ knowledge of stunting prevention, strengthen the role of Posyandu cadres, and promote sustainable education through community-based digital media. The program was implemented through three main activities is face-to-face education for mothers of toddlers at three Posyandu (Parak Alah, Seberang Air, and Koto Parak); the “Friends of Posyandu Cadres” program to enhance cadres’ skills in growth monitoring and recording; and the establishment of a “Let’s Prevent Stunting” WhatsApp group as a platform for continuous communication and education. The results showed increased knowledge and awareness among mothers regarding balanced nutrition and appropriate parenting practices, with 85–90% of participants demonstrating improved post-test scores. Cadres also showed better skills in implementing the five steps of Posyandu. Additionally, the digital platform functioned effectively as a follow-up educational tool. These findings indicate that the program contributes to strengthening community-based primary health services and supports more comprehensive and sustainable stunting prevention efforts.